An Analysis of the Operations Management of a Small and Medium Sized Enterprise (SME) - A Case Study of a Manufacturing Company in Singapore - Abdul Azim, Azrina (2006)
In today competitive business environment, there are many manufacturing philosophies and best practices that organizations can make the most of, as a platform to achieve its overall business goals and objectives. This case study dissertation is thus an attempt to analyze fundamentals of operations managements and strategy, and the significance of the management tools from the perspective of a small manufacturing enterprise. It is with the proposition that with appropriate adoption and implementation of operations management philosophies and tools, the company under study will be able to enhance its manufacturing performances, i.e. improved delivery lead time, work-in-progress (WIP), inventory, cost of production and manufacturing quality (scrap and rework), and productivity level, and consequently achieved its strategic business objectives of further company expansion, in a more efficient and effective manner.